Trait emotional intelligence as buffer of mood of in-service and pre-service teachers of preschool and elementary education during the impact of COVID-19 - Martínez Saura, Helena Fuensanta; Sánchez-López, María Cristina; Pérez-González, Juan Carlos (Anales de Psicología / Annals of Psychology, 2023)
Background: Trait Emotional Intelligence (EI) is a personal characteristic that can act as a buffer factor against vital challenging circumstances and be a predictor of mood in a variety of natural situations such as those derived from the social context of the COVID-19 pandemic. The general aim of this research was to study the relationship between trait EI and teacher moods during confinement. Method: The study included 478 participants, 316 Preschool teachers and Elementary teachers from public centers in the Region of Murcia and 162 university students of Preschool and Elementary education degrees. The instrument used to assess trait EI was the TEIQue-SF; to assess the moods experienced during the impact of COVID-19, a short version of the POMS was used. Results: Teachers with high trait EI were perceived to be more energized and kinder, as well as less nervous, moody, sad and tired, just the opposite pattern of teachers with a low trait EI profile. In addition, female teachers obtained higher scores in negative mood states. Conclusions: Although the study is correlational, the results support the idea of trait EI as a protective factor against stress, which reinforces its role as a promoter of teacher well-being.